Effect of Current on the Dynamic Motion of Truss Spar Platforms - Kurian, V.J. (2012)
Abstract—Truss spar platform is the second spar development concept that replaces the cylindrical lower section of a classic spar with an open truss structure that includes heave plates. In this paper, the dynamic responses of the Marlin truss spar in regular waves and current are presented. A MATLAB code named TRSPAR was developed for the dynamic analysis of the structure. The structure was modeled as a rigid body with three degrees of freedom. The hyperbolic extrapolation and the extended Morison equation for an inclined cylinder were used for simulating the sea state and for determining the dynamic force vector. Time domain integration using Newmark Beta method was employed. The simulated results show very little effect of the current on the response amplitude. However, it caused significant increase in the surge mean offset. Keywords- truss spar; dynamic analysis; time domain; hydrodynamic responses; rigid body